GAYA BAHASA DIALOG NABI MUSA DAN NABI KHIDR DALAM SURAH AL-KAHFI(KAJIAN STILISTIKA AL-QUR’AN) - Mohammad Arif Taufiqurrohman; Afif Kholisun Nashoih (Al-Lahjah, 2021)
Abstrak Al-Quran is an unlimited source of knowledge. The beautiful style of language that holds a million meanings becomes a magnet for the intellectuals. various phenomena of events from the stories of the Prophets are still a scientific mystery, including the story of the Prophet Moses and the Prophet Khidr. The dialogue between the two has deep meaning. This study aims to prove the beauty of the language of the Qur'an from the dialogue of the two in Surah al-Kahf verses 66-82. The research method used is library research. The data collection method applied is document analysis. The results of this study are expressions with declarative mode which have several meanings, namely threats and warnings, promises, praise, punishment, warning of differences in level, and showing weakness and respect. Imperative sentences show the meaning of pleas for mercy and pleas. Also found imperative sentences with a pattern of prohibition. Interrogative sentences have a number of meanings, including petition, denial, determination and innuendo as well as confirmation and reinforcement. The editorial of Tikrar or repetition uses the redaction of lafadz repetition and mufid meaning, and shows the meaning of tafannun, namely variation. Keyword: stylistic, dialogue, al-Kahf